Numerical and Physical Modeling of Steel Flow Behavior in the Two Strand Tundish During Nonconventional Pouring Conditions - A. Cwudziński; B. Bul'ko; P. Demeter (Archives of Foundry Engineering)
Tundish is a flow reactors, hence there is a strong correlation between its flow control devices such as dam, subflux flow controller, gas permeable barrier or advanced ladle shroud equipped, its shape of the internal working volume and the number of outlets visible in the formation of individual hydrodynamic structures. During numerical and physical simulations, the process of continuous steel casting of two slabs with dimensions of 1.15 m × 0.225 m at a speed of 1 m/min was simulated. Two-strand tundish with and without subflux flow controller (SFC) was tested. Off-centered location of subflux flow controller and ladle shroud misalignment in the tundish pouring zone were investigated. Basis on the obtained results the non-standard interaction of the feed stream with the SFC working space revealed the occurrence of a favorable hydrodynamic structure in the tundish working space in the context of limiting the stagnation flow. This is show by the formed hydrodynamic structure consists of vertically circulating streams of liquid steel, effectively eliminating and limiting the impact of reverse streams.